The protective effect of common fig (Ficus carica L.) leaves extract on testes of white rats (Rattus norvegicus) against paracetamol (Acetaminophen) drug - Noori Taha Alkhafaji; Waad Sabri Shaher (Tikrit Journal of Pure Science, 2022)
Aim: This study to investigate the protective effect of Ficus carica leaves extract against the effect of paracetamol.